Aprender ciências brincando: proposta de jogos didáticos para o 6º ano do Ensino Fundamental. - SARAIVA, Luane de Cassia Costa (2023)
The current scenario of education has undergone numerous transformations over the years, which include dynamic activities in the school context. Given this, the present work aims to analyze the contributions of the use of didactic games in the teaching-learning process for science teaching it is characterized as qualitative research, regarding the procedures it is identified as action research. Therefore, an intervention and application of three didactic games was carried out in two classes of the 6th year of Elementary School, both at the public Elementary School Dr. Mariano Antunes, located on Travessa Valparaíso in the city of Viseu-PA. In this context, it is notorious the importance of the teacher within the teaching process and mainly as an instructor in the creation of means (methodologies and didactics) that can corroborate in facing challenges and minimizing their correlated problems.